Penerapan Asas Legalitas Materil Terhadap Hukum Pidana Adat: Studi Tana Toa Kajang - Fakhrul Fuad; Hambali Thalib; Zainuddin Zainuddin (Magister Ilmu Hukum Universitas Muslim Indonesia, 2021)
The research objective is to analyze the applicable customary criminal law, as well as the principles of national criminal law contained in the customary criminal law in Tana Toa Kajang, and to analyze the prospects for the application of the principle of material legality to customary criminal law in Tana Toa Kajang in the Criminal Law Reform in Indonesia. The research method used is sociological or empirical legal research. The results of the research show that the material customary criminal law applicable in Tana Toa Kajang is about customary criminal acts and their sanctions. The implementation of customary criminal law in Tana Toa Kajang, is carried out by holding a deliberation called the abborong which is led by Ammatoa and other customary stakeholders. The principles of national criminal law contained in the customary criminal law in Tana Toa Kajang are the principle of ultimum remedium, deliberation, principle, active national / personality, principle of national / passive protection, principle of territoriality, prospects of applying the principle of material legality to the applicable customary criminal law. in Tana Toa Kajang, not all customary criminal acts that apply in Tana Toa Kajang can be processed in court because there is a parameter of the principle of material legality, which is not against Pancasila.